ANALYSIS OF CHILDREN’S DENTAL STATUS AND PARENTAL BEHAVIOR IN UTILIZING DENTAL HEALTH SERVICES BASED ON SOCIODEMOGRAPHICS IN BATU CITY BATU CITY - Merlya, Merlya; Hartami, Edina; Dewi, Candra (Universitas Brawijaya, 2025)
Dental caries affects over 2 billion children, with a global prevalence of 29%, according to WHO data. In Indonesia, high caries rates among school-aged children highlight the need for early detection tools that go beyond clinical symptoms and consider behavioral and environmental risk factors. The purpose of this study was to analyze the dental health status of children and parental behavior in utilizing children’s dental health services, with reference to sociodemographic characteristics in Batu City. A quantitative research design, descriptive and analytical approaches. Population were the total number of primary school students in Batu City was 15,243, and the number of parents was assumed to be equal.As sample comprised 299 students and their parents, proportionally distributed across the three districts. The prevalence of dental caries among primary school students is relatively high, aged 6–9 years, the DMFT index for permanent teeth showed considerable variation, with 17.3% (14 students) having DMFT of 12, and 11.1% (9 students) DMFT of 10, for primary teeth, the dmft index was also varied: 22.7% (5 students) scored 8, 18.2% (4 students) scored 3, and 13.6% (3 students) scored 6. Parental behavior regarding the utilization of dental health services in Batu City is generally limited to seeking treatment only when problems occur. Regular preventive visits are rare. School-based dental health programs are underutilized. Routine collective tooth-brushing activities were almost entirely absent in the surveyed schools in Batu City. Sociodemographic factors of parents—including educational attainment, age, and employment status—were found to influence both children’s dental health status and parental behavior in utilizing dental health services.